The Civil War Letters of Joshua K. Callaway - Callaway, Joshua K. (Book collections on Project MUSE., 1997)
Callaway was a schoolteacher, husband, and father of two when he enlisted in the 28th Alabama Infantry Regiment at the age of twenty-seven. Serving with the Army of the Tennessee, he campaigned in Mississippi, Kentucky, Tennessee, and north Georgia. Along the way this perceptive observer and gifted writer wrote a continuous narrative detailing the activities, concerns, hopes, fears, discomforts, and pleasures of a Confederate soldier in the field. Whether writing about combat, illness, encampments, or homesickness, Callaway makes even the everyday aspects of soldiering interesting. This large collection, seventy-four letters in all, is a valuable historical reference that provides new insights into life behind the front lines of the Civil War.